한국거주 중국인들의 인터넷 쇼핑몰에서의 구매요인이 고객만족, 재구매의도에 미치는 영향에 관한 연구 - 김문홍; Kim, Moon-Hong (Journal of distribution science, 2016)
Purpose - This study examines the effects of purchasing factors of consumers based on customer satisfaction and repurchasing intention buying through Internet shopping malls. The subject of this study are Chinese residents who have lived over a year in Korea. Research design, data, and methodology - In this study, former research related with internet shopping malls' customer satisfaction and repurchase intention was revised. Based on past research, the internet shopping mall purchasing factors divided to 4 factors; factors of product, price, service, and promotion. 5 hypotheses were made. They are Product factors of internet shopping malls have meaningful effect to customer satisfaction, Price factors of internet shopping malls have meaningful effect to customer satisfaction, Service factors of internet shopping malls have meaningful effect to customer satisfaction, Promotion factors of internet shopping malls have meaningful effect to customer satisfaction, Customer satisfaction factors of internet shopping malls have meaningful effect to customer repurchase intention. Measurements developed 4~5 items to each factor and questionnaires were made. The survey was conducted on 1,000 Chinese people. Out of 292 surveys, 9 were excluded which responded nothing or were unfilled. Finally 283 surveys were used in empirical analysis with SPSS 22.0 statistical program. Hypotheses were verified by structural equation modeling. Results - The following conclusions are shown in the empirical study. First, the service and promotion factors of internet shopping mall have effects on customer satisfaction. Second, customer (Chinese people who live in Korea) satisfaction have effects on repurchase intention. Third, the products value and price level of internet shopping mall have strong effects on repurchasing intention. Conclusions - There are suggestions that Chinese customers satisfied with Korean internet shopping malls might increase their royalty to the shopping malls as possibility of repurchase arises. This study has differentiating points with preceding researches that subjected residents in Korea. But there are limitations that this study also used purchasing factors used in preceding studies. Also this study has limitations, such as generalization in global market circumstances because this study subjected only Chinese people and not global customers. Therefore, further study executed complementary with those limitations would be an interesting study.